Introduction: negotiating the promotion of democracy. Issue 5 (4th July 2019) - Poppe, Annika Elena; Leininger, Julia; Wolff, Jonas
ABSTRACT: This article makes the case for why we should turn to studying democracy promotion negotiation, outlines the research questions guiding this special issue, identifies overarching findings and summarizes the individual contributions. After outlining the rationale for more attention to the issue of negotiation, which we understand as a specific form of interaction between external and local actors in democracy promotion, we outline three basic assumptions informing our research: (1) Democracy promotion is an international practice that is necessarily accompanied by processes of negotiation. (2) These negotiation processes, in turn, have an impact upon the practice and outcome of democracy promotion. (3) For external democracy promotion to be mutually owned and effective, genuine negotiations between 'promoters' and 'local actors' are indispensable; the term 'genuine' here being understood as including a substantial exchange on diverging values and interests. The article, then, introduces the three research questions for this agenda, concerning the issues on the negotiation table, the parameters shaping negotiation processes, and the results of democracy promotion negotiation. We conclude by presenting an overview of the overarching findings of the special issue as well as with brief summaries of the individual contributions.